Effects of super-dosing phytase in diets with adequate phosphorus on finishing pig growth performance and carcass characteristics - Langbein, Kari Beth; Woodworth, Jason C.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S.; DeRouchey, Joel M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 274 finishing pigs (PIC 1050 × 327, initially 129 lb) were used in a 78-d study to compare the effects of adding high levels of three different sources of phytase (super-dosing) on growth performance and carcass characteristics of finishing pigs. Pigs were randomly allotted to pens with 7 or 8 pigs per pen and 9 replications per treatment. Dietary treatments included a corn-soybean meal–based control diet that was formulated to meet the available P requirements of the pigs without any added phytase, or three diets that were formed by adding 2,000 FTU/kg of phytase from 1 of 3 different phytase sources to the basal diet. The three phytase sources were Quantum Blue 5 G (AB Vista, Chesterfield, MO), Ronozyme HiPhos (GT) 2500 (DSM Nutritional Products, Parsippany, NJ), or Optiphos 1000 (Enzyvia, Sheraton, IN). Overall, regardless of source, super-dosing phytase had no effect (P > 0.26) on ADG, ADFI, or F/G; furthermore, there were no effects (P > 0.36) on any of the carcass criteria measured. In conclusion, in this environment with nutritionally adequate diets, this study suggests that super-dosing phytase had no beneficial effects on finishing pig growth or carcass performance.
Keywords: Phosphorous; Phytase; Finishing pig